Toner for electrostatic charge image development and method for manufacturing the same
The development of a toner with a core-shell structure using amorphous polyester resins and a block copolymer addresses the issue of low electrostatic properties and image fog in electrophotographic methods, achieving high-quality image development.
Patent Information
- Application Number
- JP2023172574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Existing toners used in electrophotographic methods for flexible packaging, such as food packaging, suffer from low electrostatic properties and tend to cause fog in images, especially when using polyester resins that do not contain bisphenol A-based components.
A toner with a core-shell structure is developed, comprising a core portion made of amorphous polyester resin A and a shell portion made of amorphous polyester resin B. The solubility parameters of the two resins have a specific difference, and a block copolymer of polyethylene glycol and polypropylene glycol is used to facilitate the aggregation and fusion process.
The resulting toner exhibits excellent charging properties and significantly reduces image fog, enabling high-quality image development in electrophotographic methods.
Smart Images

Figure 2025063414000001 
Figure 2025063414000002 
Figure 2025063414000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner for developing electrostatic images used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like, and a method for producing the same. [Background technology]
[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of electrophotographic toners that can meet the demands of higher image quality and higher speeds. In order to meet the demands of higher image quality, a method for obtaining a toner that has a narrow particle size distribution, a small particle size, and a fixing property that can meet the demands of higher speeds is being carried out, in which fine resin particles or the like are aggregated and fused in an aqueous medium to obtain a toner, namely, a chemical toner, which is produced by an aggregation and fusion method (emulsion aggregation method, aggregation and coalescence method). Chemical toners can achieve precise control of toner structure by agglomerating fine particles in water, for example, toners having a so-called core-shell structure can be produced.
[0003] Patent Document 1 describes a toner containing a large number of toner particles, the toner particles having a core region and a shell region that covers the outer periphery of the core region and has a different composition from the core region, the core region and the shell region are each made of a material containing a resin and a colorant, and the concentration of the colorant in the core region is expressed as C C [wt%], the concentration of the colorant in the shell region is C S When [wt%] is used, C C ≦C S A toner characterized by satisfying the following relationship is disclosed. Patent Document 2 discloses a toner that is composed of toner particles having a core region containing a resin material and a colorant, and a shell region that covers the core region and has a composition different from that of the core region, the toner particles having an average value (average circularity) of circularity R of 0.92 or more, and containing 0.05 to 0.6 wt % of an alkylbenzenesulfonate having a linear alkyl group in the shell region. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-89913 A [Patent Document 2] JP 2008-129282 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, the demand for electrophotographic printing has been increasing even in the field of printing on flexible packaging such as food packaging, and from the viewpoint of stricter safety, toners using polyester resins that do not contain structural units derived from bisphenol A-based components are being developed. However, such toners have low electrostatic properties, and when printed using such toners, fogging tends to occur on the image. The present invention relates to a toner for developing electrostatic images which has excellent charging properties and gives images with little fog, and a method for producing the toner. [Means for solving the problem]
[0006] The present inventors have found that, in producing a toner by an aggregation fusion method, by aggregating resin particles containing an amorphous polyester resin A having a specific structure in the presence of a surfactant having a specific structure to obtain aggregated particles 1, by adding an amorphous polyester resin B having a specific structure to the aggregated particles 1 to obtain aggregated particles 2 having a core-shell structure, and by having the solubility parameters of the amorphous polyester resins A and B satisfy a specific relationship, a toner for developing electrostatic images which has excellent charging properties and gives images with little fog can be obtained. The present invention relates to the following [1] and [2]. [1] A method for producing a toner for developing electrostatic images having a core-shell structure comprising a core portion containing an amorphous polyester resin A and a shell portion containing an amorphous polyester resin B, comprising the steps of: The amorphous polyester resins A and B are polycondensates of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, Solubility parameter SP of amorphous polyester resin B B and the solubility parameter SP of amorphous polyester resin A A Difference with ΔSP B-A is between 0.4 and 1.5, A method for producing a toner for developing electrostatic images, comprising the following steps 1 to 3 in this order: Step 1: A step of aggregating resin particles X containing an amorphous polyester resin A in an aqueous medium in the presence of a block copolymer of polyethylene glycol and polypropylene glycol to obtain aggregated particles 1. Step 2: A step of adding resin particles Y containing an amorphous polyester resin B to the aggregated particles 1 obtained in step 1 to obtain aggregated particles 2. Step 3: A step of fusing the aggregated particles 2 obtained in step 2 to obtain fused particles. [2] A toner for developing electrostatic images having a core-shell structure comprising a core portion containing an amorphous polyester resin A and a shell portion containing an amorphous polyester resin B, The amorphous polyester resins A and B are polycondensates of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, Solubility parameter SP of amorphous polyester resin B B and the solubility parameter SP of amorphous polyester resin A A Difference with ΔSP B-A is between 0.4 and 1.5, A toner for developing electrostatic images, comprising a block copolymer of polyethylene glycol and polypropylene glycol interposed between a core portion and a shell portion. Effect of the Invention
[0007] According to the present invention, there are provided a toner for developing electrostatic images, which has excellent charging properties and gives images with little fog, and a method for producing the toner. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Method of manufacturing toner for developing electrostatic images] The method for producing a toner for developing electrostatic images of the present invention (hereinafter, also simply referred to as the "production method") is a method for producing a toner for developing electrostatic images having a core-shell structure consisting of a core portion containing an amorphous polyester resin A and a shell portion containing an amorphous polyester resin B, in which the amorphous polyester resins A and B are polycondensates of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, and the solubility parameter SP B and the solubility parameter SP of amorphous polyester resin A A Difference with ΔSP B-A is 0.4 or more and 1.5 or less, and the method includes the following steps 1 to 3 in this order. Step 1: A step of aggregating resin particles X containing an amorphous polyester resin A in an aqueous medium in the presence of a block copolymer of polyethylene glycol and polypropylene glycol to obtain aggregated particles 1. Step 2: A step of adding resin particles Y containing an amorphous polyester resin B to the aggregated particles 1 obtained in step 1 to obtain aggregated particles 2. Step 3: A step of fusing the aggregated particles 2 obtained in step 2 to obtain fused particles. By the above-mentioned production method, it is possible to obtain a toner for developing electrostatic images which has excellent charging properties and gives images with little fog.
[0009] The detailed mechanism by which the manufacturing method of the present invention can provide a toner for developing electrostatic images (hereinafter, also simply referred to as "toner") that has excellent charging properties and can produce images with little fog is not clear, but is thought to be as follows. In the manufacturing method of the present invention, in step 1, resin particles X containing an amorphous polyester resin A are aggregated in an aqueous medium in the presence of a block copolymer of polyethylene glycol and polypropylene glycol to obtain aggregated particles 1. Since the amorphous polyester resin A is a polycondensation product of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, the hydrophobic polypropylene glycol block moiety in the block copolymer is adsorbed to the surface of the aggregated particles 1, and a core part is formed in which the hydrophilic polyethylene glycol block moiety spreads from the surface of the aggregated particles 1 toward the water side. That is, the block copolymer is adsorbed to the core part and functions as a dispersant for the aggregated particles 1. Then, in step 2, an amorphous polyester resin B, which is a polycondensation product of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, is added to the core part to which the block copolymer is adsorbed to form a shell part. Solubility parameter SP of amorphous polyester resin B B is the solubility parameter SP of amorphous polyester resin A A Greater than and SP B and SP A It is believed that the above-mentioned effect is achieved because, when the difference between the polarity and the molecular weight is 0.4 or more and 1.5 or less, the shell portion, which has a relatively high polarity, is not compatible with the core portion, and the shell portion interacts with the polyethylene glycol block of the block copolymer in an affinity manner, thereby forming a core-shell structure in which the shell portion is not separated from the core portion. The above-mentioned mechanism regarding the effect of the present invention is merely a presumption, and the present invention is not limited thereto.
[0010] The definitions of various terms used in this specification are given below. Whether a resin is crystalline or amorphous is determined by the crystallinity index. The crystallinity index is defined as the ratio of the softening point of the resin to the maximum endothermic peak temperature (softening point (°C) / maximum endothermic peak temperature (°C)) in the measurement method described in the examples below. A crystalline resin is one with a crystallinity index of 0.6 or more and 1.4 or less. An amorphous resin is one in which no endothermic peak is observed, or, if observed, has a crystallinity index of less than 0.6 or more than 1.4. The crystallinity index can be appropriately adjusted by the types and ratios of raw material monomers, as well as production conditions such as reaction temperature, reaction time, and cooling rate. The carboxylic acid component of the polyester resin includes not only the compound itself, but also anhydrides that decompose during the reaction to generate an acid, and alkyl esters of each carboxylic acid (alkyl groups having 1 to 3 carbon atoms). Volume Median Particle Size (D 50 )" is the particle size at which the cumulative volume frequency calculated by volume fraction is 50% starting from the smallest particle size. The coefficient of variation of particle size distribution (hereinafter, simply referred to as "CV value") is a value expressed by the following formula: In the following formula, the volume average particle size is the particle size obtained by multiplying the particle size measured on a volume basis by the proportion of particles having that particle size value, and dividing the resulting value by the number of particles. CV value (%) = [Standard deviation of particle size distribution (μm) / Volume average particle size (μm)] x 100
[0011] <Process 1> In step 1, resin particles X containing an amorphous polyester resin A are aggregated in an aqueous medium in the presence of a block copolymer of polyethylene glycol and polypropylene glycol to obtain aggregated particles 1. Here, in addition to the resin particles X, it is preferable to aggregate colorant particles and release agent particles, and it is more preferable to mix a resin particle dispersion X containing the resin particles X, a colorant particle dispersion, and a release agent particle dispersion to aggregate these particles. [Resin particles X] The resin particle dispersion X used in step 1 contains resin particles X. The resin particles X contain an amorphous polyester resin A. From the viewpoint of low-temperature fixability of the resulting toner, the resin particles X may contain the amorphous polyester resin A and the crystalline polyester resin C in the same or different particles.
[0012] <Amorphous polyester resin A> The amorphous polyester resin A (hereinafter, simply referred to as "resin A") is a polycondensate of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound. The amorphous polyester resin A may be a modified polyester resin. Examples of the modified polyester resin include a urethane modified polyester resin, an epoxy modified polyester resin, and a composite resin containing a polyester resin segment and an addition polymerization resin segment.
[0013] The alcohol component contains 80 mol % or more of an aliphatic diol. The aliphatic diol preferably has 2 or more, more preferably 3 or more, and preferably has 16 or less, more preferably 12 or less, and further preferably 8 or less. Examples of the aliphatic diol include α,ω-aliphatic diols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol; and aliphatic diols other than α,ω-aliphatic diols such as 1,2-propanediol and neopentyl glycol. Among these, 1,2-propanediol and neopentyl glycol are preferred, and neopentyl glycol is more preferred.
[0014] The amount of the aliphatic diol in the alcohol component is 80 mol% or more, preferably 85 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, preferably 100 mol%.
[0015] From the viewpoints of the electrostatic chargeability of the toner and reducing fog in the resulting image, the amount of neopentyl glycol in the alcohol component is preferably 60 mol % or more, more preferably 70 mol % or more, even more preferably 80 mol % or more, and even more preferably 90 mol % or more, and 100 mol % or less.
[0016] The alcohol component may contain other alcohol components different from the aliphatic diol. Examples of the other alcohol components include alkylene oxide adducts of aromatic diols such as alkylene oxide adducts of bisphenol A, and trihydric or higher alcohols such as glycerin, pentaerythritol, and trimethylolpropane. The alcohol component may be used alone or in combination of two or more.
[0017] Examples of the carboxylic acid component include dicarboxylic acids and polycarboxylic acids having three or more carboxylic acids.
[0018] Examples of dicarboxylic acids include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, aromatic dicarboxylic acids are preferred.
[0019] Examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred. The amount of the aromatic dicarboxylic acid in the carboxylic acid component is preferably 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, and is preferably 100 mol % or less, preferably 100 mol %.
[0020] The aliphatic dicarboxylic acid preferably has 2 or more, more preferably 3 or more, and preferably has 30 or less, more preferably 20 or less. Examples of aliphatic dicarboxylic acids include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, azelaic acid, and succinic acid substituted with an aliphatic hydrocarbon group having from 1 to 20 carbon atoms. Examples of succinic acid substituted with an aliphatic hydrocarbon group having from 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. When the carboxylic acid component contains an aliphatic dicarboxylic acid, the amount of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 5 mol % or more, more preferably 10 mol % or more, even more preferably 15 mol % or more, and preferably 40 mol % or less, more preferably 30 mol % or less, even more preferably 20 mol % or less.
[0021] An example of the alicyclic dicarboxylic acid is cyclohexanedicarboxylic acid.
[0022] The trivalent or higher polyvalent carboxylic acid is preferably a trivalent carboxylic acid, such as trimellitic acid. The carboxylic acid component may be used alone or in combination of two or more.
[0023] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0024] <Method for producing amorphous polyester resin A> Resin A is produced by a method of polycondensing an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component. In this reaction, if necessary, an esterification catalyst such as tin(II) di(2-ethylhexanoate), dibutyltin oxide, or titanium diisopropylate bistriethanolamine may be used in an amount of 0.01 part by mass or more and 5 parts by mass or less per 100 parts by mass of the combined amount of the alcohol component and the carboxylic acid component; or an esterification promoter such as gallic acid (equivalent to 3,4,5-trihydroxybenzoic acid) may be used in an amount of 0.001 part by mass or more and 0.5 part by mass or less per 100 parts by mass of the combined amount of the alcohol component and the carboxylic acid component. When a monomer having an unsaturated bond such as fumaric acid is used in polycondensation, a radical polymerization inhibitor may be used, if necessary, in an amount of preferably 0.001 to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. An example of the radical polymerization inhibitor is 4-tert-butylcatechol. The reaction temperature is preferably 120° C. or higher, more preferably 150° C. or higher, even more preferably 170° C. or higher, and is preferably 250° C. or lower, more preferably 240° C. or lower. The reaction may be carried out in an inert gas atmosphere.
[0025] (Physical properties of amorphous polyester resin A) The softening point of the amorphous polyester resin A is preferably 70° C. or higher, more preferably 80° C. or higher, even more preferably 90° C. or higher, and even more preferably 100° C. or higher, from the viewpoint of the storage stability of the toner, and is preferably 140° C. or lower, more preferably 130° C. or lower, and even more preferably 120° C. or lower, from the viewpoint of the low-temperature fixing ability of the toner.
[0026] The glass transition temperature of the amorphous polyester resin A is preferably 30° C. or higher, more preferably 40° C. or higher, and even more preferably 50° C. or higher, from the viewpoint of the storage stability of the toner, and is preferably 80° C. or lower, more preferably 75° C. or lower, and even more preferably 70° C. or lower, from the viewpoint of the low-temperature fixing ability of the toner.
[0027] The acid value of the amorphous polyester resin A is preferably 2 mgKOH / g or more, more preferably 5 mgKOH / g or more, even more preferably 10 mgKOH / g or more, even more preferably 15 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 35 mgKOH / g or less, even more preferably 30 mgKOH / g or less.
[0028] Solubility parameter (SP) of amorphous polyester resin A A (cal / cm 3 ) 1 / 2 From the viewpoint of the chargeability of the toner and reduction of fog in the obtained image, the toner charge is preferably 10.7 (cal / cm 3 ) 1 / 2 More preferably, 10.9 (cal / cm 3 ) 1 / 2 More preferably, 11.1 (cal / cm 3 ) 1 / 2 and preferably 12.0 (cal / cm 3 ) 1 / 2 Less than or equal to 11.8 (cal / cm 3 ) 1 / 2 More preferably, 11.6 (cal / cm 3 ) 1 / 2 The following is the result. The solubility parameter of the amorphous polyester resin A is a solubility parameter according to the Fedors method.
[0029] The softening point, glass transition temperature, acid value, and solubility parameter of the amorphous polyester resin A can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, and cooling rate. The softening point, glass transition temperature, and acid value of the amorphous polyester resin A can be determined by the method described in the examples. When two or more kinds of amorphous polyester resins A are used in combination, the softening point, glass transition temperature, and acid value of the mixture are preferably within the above-mentioned ranges. As for the solubility parameter, it is sufficient that any one of the resins A is within the above-mentioned range, and it is preferable that all the resins A are within the above-mentioned range.
[0030] The content of the amorphous polyester resin A in the resin particles X is preferably 60% by mass or more, more preferably 65% by mass or more, even more preferably 70% by mass or more, still more preferably 75% by mass or more, and is 100% by mass or less. From the viewpoints of the electrostatic chargeability of the toner and reducing fog in the obtained images, the content of the amorphous polyester resin A in the toner particles is preferably 40% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, and is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less.
[0031] <Crystalline polyester resin C> The crystalline polyester resin C is, for example, a polycondensate of an alcohol component and a carboxylic acid component. The alcohol component is preferably an α,ω-aliphatic diol. The α,ω-aliphatic diol has preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, and preferably 16 or less, more preferably 14 or less, even more preferably 12 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, ethylene glycol is preferred.
[0032] The amount of the α,ω-aliphatic diol in the alcohol component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, even more preferably 100 mol%.
[0033] The alcohol component may contain other alcohol components different from the α,ω-aliphatic diol. Examples of the other alcohol components include aliphatic diols other than the α,ω-aliphatic diols, such as 1,2-propanediol and neopentyl glycol, aromatic diols, such as alkylene oxide adducts of bisphenol A, and trihydric or higher alcohols, such as glycerin, pentaerythritol, and trimethylolpropane. The alcohol component may be used alone or in combination of two or more.
[0034] The carboxylic acid component is preferably an α,ω-aliphatic dicarboxylic acid, and more preferably a linear aliphatic dicarboxylic acid. The α,ω-aliphatic dicarboxylic acid has preferably 4 or more, more preferably 8 or more, even more preferably 10 or more, and preferably 14 or less, more preferably 12 or less. Examples of the α,ω-aliphatic dicarboxylic acid include fumaric acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among these, sebacic acid is preferred.
[0035] The carboxylic acid component may include a monocarboxylic acid having a hydrocarbon group. From the viewpoint of obtaining a toner having excellent electrostatic properties and capable of suppressing the occurrence of fog, the number of carbon atoms in the hydrocarbon group of the monocarboxylic acid is 9 or more, preferably 10 or more, more preferably 13 or more, and even more preferably 15 or more, and is 24 or less, preferably 23 or less, and more preferably 21 or less. Examples of the hydrocarbon group include aliphatic hydrocarbon groups such as alkyl groups, alkynyl groups, and alkenyl groups, of which alkyl and alkenyl groups are preferred, and alkyl groups are more preferred. The hydrocarbon group may be branched or linear. Examples of monocarboxylic acids having a hydrocarbon group having from 9 to 24 carbon atoms include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, etc. Among these, from the viewpoint of obtaining a toner having excellent chargeability and capable of suppressing the occurrence of fogging, preferred are lauric acid, stearic acid, and behenic acid, and more preferred are stearic acid.
[0036] The carboxylic acid component may contain other carboxylic acid components different from the aliphatic dicarboxylic acid. Examples of the other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid, and polycarboxylic acids having three or more valences. The carboxylic acid component may be used alone or in combination of two or more.
[0037] The amount of α,ω-aliphatic dicarboxylic acid in the carboxylic acid component is preferably 75 mol % or more, more preferably 80 mol % or more, even more preferably 85 mol % or more, and is preferably 99 mol % or less, more preferably 95 mol % or less.
[0038] The amount of monocarboxylic acid having a hydrocarbon group having 9 to 24 carbon atoms in the carboxylic acid component is preferably 1 mol % or more, more preferably 5 mol % or more, and preferably 25 mol % or less, more preferably 20 mol % or less, and even more preferably 15 mol % or less.
[0039] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0040] The crystalline polyester resin C can be produced, for example, by the same method as that for the amorphous polyester resin A described above.
[0041] (Physical properties of crystalline polyester resin C) The softening point of the crystalline polyester resin C is preferably 60°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher from the viewpoint of the storage stability of the toner, and is preferably 130°C or lower, more preferably 110°C or lower, and even more preferably 90°C or lower from the viewpoint of the low-temperature fixing ability of the toner. The melting point of the crystalline polyester resin C is preferably 55°C or higher, more preferably 60°C or higher, and even more preferably 65°C or higher from the viewpoint of the storage stability of the toner, and is preferably 100°C or lower, more preferably 90°C or lower, and even more preferably 80°C or lower from the viewpoint of the low-temperature fixing ability of the toner.
[0042] The acid value of the crystalline polyester resin C is preferably 2 mgKOH / g or more, more preferably 5 mgKOH / g or more, and preferably 25 mgKOH / g or less, more preferably 20 mgKOH / g or less, and even more preferably 15 mgKOH / g or less. The softening point, melting point and acid value of the crystalline polyester resin C can be appropriately adjusted by the type and amount of the raw material monomer, as well as production conditions such as reaction temperature, reaction time and cooling rate, and are determined by the method described in the Examples below. When two or more types of crystalline polyester resin C are used in combination, it is preferable that the softening point, melting point and acid value obtained as a mixture thereof are each within the above-mentioned ranges.
[0043] When the resin particles X contain the crystalline polyester resin C, the content of the crystalline polyester resin C in the resin particles X is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less. When the resin particles X contain the crystalline polyester resin C, the mass ratio of the amorphous polyester resin A to the crystalline polyester resin C in the resin particles X [amorphous polyester resin A / crystalline polyester resin C] is preferably 60 / 40 or more, more preferably 70 / 30 or more, and is preferably 95 / 5 or less, more preferably 90 / 10 or less. When the resin particles X contain the crystalline polyester resin C, the content of the crystalline polyester resin C in the toner particles is, from the viewpoint of low-temperature fixability, preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 35% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0044] [Block copolymer of polyethylene glycol and polypropylene glycol] The block copolymer of polyethylene glycol and polypropylene glycol (hereinafter also simply referred to as "block copolymer") may be a block copolymer having at least one polyethylene glycol segment and at least one polypropylene glycol segment, but is preferably a polyethylene glycol-polypropylene glycol-polyethylene glycol type triblock copolymer, more preferably a triblock copolymer represented by the following formula (1), and even more preferably a triblock copolymer represented by the following formula (2).
[0045] [ka]
[0046] In formula (1), R 1 and R 2 each independently represents a hydrogen atom or a hydrocarbon group having from 1 to 24 carbon atoms. The hydrocarbon group may be linear or branched. R 1 and R 2 is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 5 carbon atoms, more preferably a hydrogen atom. R 1 and R 2 Examples of the alkyl group having 1 to 5 carbon atoms that can be used in a preferred embodiment include a methyl group, an ethyl group, various propyl groups, various butyl groups, and various pentyl groups. In formula (1), x and z represent the average number of moles of ethylene oxide added, and y represents the average number of moles of propylene oxide added. x, y, and z are each independently 1 or more and 500 or less, preferably 20 or more and 300 or less. In addition, the ratio of the sum of x and z to y [(x+z) / y] is preferably 0.1 or more and 7.0 or less.
[0047] [ka]
[0048] In formula (2), m represents the average number of moles of propylene oxide added, and n represents the average number of moles of ethylene oxide added. m is 10 or more, preferably 20 or more, and 80 or less, preferably 70 or less. n is 1 or more, preferably 20 or more, more preferably 40 or more, even more preferably 65 or more, even more preferably 75 or more, and is 200 or less, preferably 170 or less. Moreover, the ratio of 2n to m (2n / m) is preferably 0.1 or more and 7.0 or less.
[0049] From the viewpoints of the electrostatic chargeability of the toner and reduction of fog in the obtained image, the content of the polyethylene glycol segment in the block copolymer of polyethylene glycol and polypropylene glycol is preferably 5% by mass or more, more preferably 30% by mass or more, even more preferably 45% by mass or more, even more preferably 60% by mass or more, even more preferably 75% by mass or more, and is preferably 90% by mass or less, more preferably 85% by mass or less.
[0050] As the block copolymer, commercially available products can also be used, and preferred examples thereof include "ADEKA (registered trademark) Pluronic F108", "ADEKA (registered trademark) Pluronic F88", "ADEKA (registered trademark) Pluronic F68", "ADEKA (registered trademark) Pluronic F87", "ADEKA (registered trademark) Pluronic P85", "ADEKA (registered trademark) Pluronic P84" and "ADEKA (registered trademark) Pluronic L81" (all manufactured by ADEKA Corporation).
[0051] The amount of the block copolymer of polyethylene glycol and polypropylene glycol added (used) in step 1 is, relative to 100 parts by mass of the total of resins A and C in resin particle X, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less.
[0052] The content of the block copolymer of polyethylene glycol and polypropylene glycol in the toner particles is, from the viewpoints of the electrostatic chargeability of the toner and reduction of fog in the obtained images, preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less.
[0053] [Method for producing resin particle dispersion X] The resin particle dispersion X containing the amorphous polyester resin A can be prepared by a known method, but it is preferable to disperse the resin particles X in an aqueous medium by a phase inversion emulsification method. Examples of the phase inversion emulsification method include a method in which an aqueous medium is added to an organic solvent solution of a resin or a molten resin to perform phase inversion emulsification.
[0054] The organic solvent used for phase inversion emulsification is not particularly limited as long as it dissolves the resin. From the viewpoint of facilitating phase inversion, examples include alcohol-based solvents such as ethanol, isopropanol, and isobutanol; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and diethyl ketone; ether-based solvents such as dibutyl ether, tetrahydrofuran, and dioxane; and acetate-based solvents such as ethyl acetate and isopropyl acetate. It is preferable to add a neutralizing agent to the organic solvent solution. Examples of the neutralizing agent include basic substances. Examples of the basic substance include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, and nitrogen-containing basic substances such as ammonia, trimethylamine, and diethanolamine. The equivalent amount (mol %) of the neutralizing agent used relative to the acid groups of the resin contained in the resin particles X is, from the viewpoints of obtaining fine resin particles and improving dispersion stability, preferably 40 mol % or more, more preferably 50 mol % or more, even more preferably 60 mol % or more, and is preferably 95 mol % or less, more preferably 90 mol % or less, even more preferably 85 mol % or less. The equivalent amount (mol %) of the neutralizing agent used can be calculated by the following formula: When the equivalent amount of the neutralizing agent used is 100 mol % or less, it is synonymous with the degree of neutralization. Equivalent amount of neutralizing agent used (mol%)=[{weight of neutralizing agent added (g) / equivalent amount of neutralizing agent} / [{weighted average acid value of resin constituting resin particle X (mgKOH / g)×weight of resin constituting resin particle X (g)} / (56×1000)]]×100
[0055] While stirring the organic solvent solution or the molten resin, the aqueous medium is gradually added to cause phase inversion. The temperature of the organic solvent solution when the aqueous medium is added is preferably 30° C. or higher, more preferably 40° C. or higher, and is preferably 90° C. or lower, more preferably 85° C. or lower. The content of the amorphous polyester resin A in the resin particles X is as described above.
[0056] After the phase inversion emulsification, if necessary, the organic solvent may be removed from the obtained dispersion by distillation, etc. In this case, the amount of the remaining organic solvent in the dispersion is preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably substantially 0% by mass.
[0057] The volume median particle size (D 50 From the viewpoint of obtaining a toner that can provide high quality images, the particle size is preferably 0.05 μm or more, more preferably 0.08 μm or more, even more preferably 0.10 μm or more, and is preferably 0.8 μm or less, more preferably 0.5 μm or less, even more preferably 0.2 μm or less. From the viewpoint of obtaining a toner that can obtain high-quality images, the CV value of the resin particles X in the dispersion is preferably 10% or more, more preferably 15% or more, and is preferably 35% or less, more preferably 30% or less. The volume median particle size of resin particle X (D 50 ) and the CV value is determined by the method described in the Examples below.
[0058] From the viewpoint of improving the productivity of the toner and the dispersion stability of the resin particle dispersion X, the solid content concentration of the resin particle dispersion X is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less. The solid content is the total amount of non-volatile components.
[0059] The resin particle dispersion X containing the amorphous polyester resin A and the crystalline polyester resin C can be obtained by the same method as described above. When the resin particle dispersion Xa containing the amorphous polyester resin A and the resin particle dispersion Xb containing the crystalline polyester resin C are mixed and used, these resin particle dispersions can be obtained by the same method as described above. The contents of the amorphous polyester resin A and the crystalline polyester resin C in the resin particles X are as described above.
[0060] [Aqueous medium] In the present invention, the aqueous medium is a medium containing water as a main component, and the water content in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more and 100% by mass or less. The water is preferably deionized water or distilled water. Examples of components other than water that can form an aqueous medium together with water include organic solvents that dissolve in water, such as alkyl alcohols having 1 to 5 carbon atoms, dialkyl ketones having 3 to 5 carbon atoms, such as acetone and methyl ethyl ketone, and cyclic ethers, such as tetrahydrofuran. Among these, alkyl alcohols having 1 to 5 carbon atoms are preferred, and methanol or ethanol are more preferred.
[0061] [Colorant Particles] In step 1, it is preferable to aggregate colorant particles containing a colorant together with the resin particles X. It is preferable that the colorant particles are mixed with the above-mentioned resin particle dispersion X as a colorant particle dispersion in which colorant particles containing a colorant are dispersed in an aqueous medium. As the colorant, any of the dyes, pigments, etc. used as toner colorants can be used. Examples of colorants include carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment green B, rhodamine B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, and disazo yellow. The toner may be either a black toner or a color toner other than black. The content of the colorant in the toner particles is preferably 1% by mass or more, more preferably 2% by mass or more, and preferably 10% by mass or less, more preferably 7% by mass or less, from the viewpoint of image density.
[0062] [Method for producing colorant particle dispersion] The colorant particles are preferably obtained as a colorant particle dispersion by dispersing a colorant and an aqueous medium using a dispersing machine such as a homogenizer, an ultrasonic dispersing machine, etc. From the viewpoint of improving the dispersion stability of the colorant, the dispersion is preferably carried out in the presence of a surfactant or an addition polymer (hereinafter, the addition polymer used to disperse the colorant is also referred to as "addition polymer E"). Examples of the surfactant include a nonionic surfactant, an anionic surfactant, and a cationic surfactant. The addition polymer E preferably has a constituent unit derived from an addition polymerizable monomer a having an aromatic group, and further preferably contains at least one selected from the group consisting of an addition polymerizable monomer b having an ionic group, an addition polymerizable monomer c having a polyalkylene oxide group, and a macromonomer d. For the colorant particle dispersion using the addition polymer E, see JP2021-026129A.
[0063] From the viewpoint of image density of the printed matter, the content of the colorant in the colorant particle dispersion is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less. The solids concentration of the colorant particle dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less.
[0064] Volume median particle size D of colorant particles 50 From the viewpoint of improving the dispersibility of the colorant in the toner, the particle size is preferably 0.05 μm or more, more preferably 0.08 μm or more, and is preferably 0.4 μm or less, more preferably 0.3 μm or less, and further preferably 0.25 μm or less. From the viewpoint of improving the dispersibility of the colorant in the toner, the CV value of the colorant particles is preferably 10% or more, more preferably 15% or more, and is preferably 40% or less, more preferably 35% or less, and even more preferably 30% or less. Volume median particle size D of colorant particles 50 and CV values are measured by the methods in the Examples.
[0065] [Release agent particles] In step 1, it is preferable to aggregate release agent particles containing a release agent together with the resin particles X and the colorant particles. The release agent particles are preferably mixed with the above-mentioned resin particle dispersion liquid X as a release agent particle dispersion liquid in which release agent particles containing a release agent are dispersed in an aqueous medium. Examples of the release agent include polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, hydrocarbon waxes such as microcrystalline wax, paraffin wax, Fischer-Tropsch wax, and oxides thereof, ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax, fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.
[0066] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, and preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 100° C. or lower.
[0067] The content of the release agent in the toner particles is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 5% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less.
[0068] [Method for producing release agent particle dispersion liquid] The release agent particle dispersion can be obtained by using a surfactant, but is preferably obtained by mixing the release agent and resin particles. By preparing the release agent particles using the release agent and resin particles, the release agent particles are stabilized by the resin constituting the resin particles, and it becomes possible to disperse the release agent in an aqueous medium without using a surfactant. It is considered that the release agent particle dispersion has a structure in which a large number of resin particles are attached to the surface of the release agent particles. The resin constituting the resin particles in which the release agent is dispersed is preferably a polyester resin, and the above-mentioned amorphous polyester resin A is preferable. In addition, a composite resin D having a polyester resin segment and an addition polymerization resin segment may be used. For the composite resin D, reference is made to JP 2021-182045 A.
[0069] Volume median particle size D of release agent particles 50 From the viewpoint of obtaining uniform aggregated particles 1 by aggregation, the average particle size is preferably 0.05 μm or more, more preferably 0.1 μm or more, even more preferably 0.2 μm or more, and is preferably 1 μm or less, more preferably 0.8 μm or less, even more preferably 0.6 μm or less. The CV value of the release agent particles is preferably 10% or more, more preferably 15% or more, and is preferably 50% or less, more preferably 45% or less. Volume median particle size D of release agent particles 50 The CV value is measured by the method described in the Examples.
[0070] Aggregated particles 1 may also contain additives such as charge control agents, magnetic powders, flowability improvers, conductivity adjusters, reinforcing fillers such as fibrous substances, antioxidants, antiaging agents, and cleaning improvers.
[0071] The resin particle dispersion X and the optional components are mixed by a conventional method. From the viewpoint of efficient aggregation, it is preferable to add an aggregating agent to the mixed dispersion obtained by the mixing.
[0072] [Flocculant] In the step of aggregating the resin particles X, it is preferable to add an aggregating agent in order to efficiently carry out the aggregation. Examples of the flocculant include cationic surfactants such as quaternary salts, organic flocculants such as polyethyleneimine, and inorganic flocculants. Examples of the inorganic flocculant include inorganic metal salts such as sodium sulfate, sodium nitrate, sodium chloride, calcium chloride, and calcium nitrate; inorganic ammonium salts such as ammonium sulfate, ammonium chloride, and ammonium nitrate; and divalent or higher metal complexes. From the viewpoint of improving the coagulation properties and obtaining uniformly coagulated particles, inorganic coagulants having a valence of 1 to 5 are preferred, inorganic metal salts having a valence of 1 to 2 and inorganic ammonium salts are more preferred, inorganic ammonium salts are even more preferred, and ammonium sulfate is even more preferred.
[0073] For example, 5 to 50 parts by mass of the aggregating agent is added to a mixed dispersion containing resin particles X, release agent particles, and colorant particles at 0° C. to 40° C., relative to 100 parts by mass of the resin in the resin particles X, and the resin particles X, release agent particles, and colorant particles are aggregated in an aqueous medium to obtain aggregated particles. Furthermore, from the viewpoint of promoting aggregation, it is preferable to increase the temperature of the dispersion after adding the aggregating agent.
[0074] Volume median particle size D of aggregate 1 50 is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less.
[0075] <Process 2> Step 2 is a step of adhering and aggregating resin particles Y containing amorphous polyester resin B to the obtained aggregated particles 1 as core parts, thereby forming shell parts to obtain aggregated particles 2. In step 2, it is preferable to add resin particle dispersion Y containing resin particles Y to the aggregated particle 1 dispersion to further adhere resin particles Y to obtain a dispersion of aggregated particles 2. The production method of the present invention, by including the step 2, can obtain toner particles having a core-shell structure. [Resin particles Y] The resin particles Y contain the amorphous polyester resin B.
[0076] <Amorphous polyester resin B> Amorphous polyester resin B (hereinafter, also simply referred to as "resin B") is a polycondensate of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound. The amorphous polyester resin B may be a modified polyester resin. Examples of the modified polyester resin include a urethane modified polyester resin, an epoxy modified polyester resin, and a composite resin containing a polyester resin segment and an addition polymerization resin segment.
[0077] The alcohol component is preferably an aliphatic diol. The aliphatic diol has preferably 2 or more, more preferably 3 or more, and preferably 8 or less, more preferably 6 or less, and further preferably 4 or less. Examples of the aliphatic diol include α,ω-aliphatic diols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol, and aliphatic diols other than α,ω-aliphatic diols such as 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, and neopentyl glycol. Among these, aliphatic diols other than α,ω-aliphatic diols are preferred, and 1,2-propanediol is more preferred.
[0078] The amount of the aliphatic diol in the alcohol component is 80 mol% or more, preferably 85 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, preferably 100 mol%.
[0079] The alcohol component may contain other alcohol components different from the aliphatic diol. Examples of the other alcohol components include alkylene oxide adducts of aromatic diols such as alkylene oxide adducts of bisphenol A, and trihydric or higher alcohols such as glycerin, pentaerythritol, and trimethylolpropane. The alcohol component may be used alone or in combination of two or more.
[0080] Examples of the carboxylic acid component include dicarboxylic acids and polycarboxylic acids having three or more carboxylic acids.
[0081] Examples of dicarboxylic acids include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, aromatic dicarboxylic acids are preferred.
[0082] Examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. The amount of aromatic dicarboxylic acid in the carboxylic acid component is preferably 50 mol% or more, more preferably 60 mol% or more, even more preferably 70 mol% or more, and is preferably 100 mol% or less, more preferably 98 mol% or less, even more preferably 95 mol%.
[0083] The aliphatic dicarboxylic acid preferably has 2 or more, more preferably 3 or more, and preferably has 30 or less, more preferably 20 or less. Examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, azelaic acid, and succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms. Examples of the succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, fumaric acid is preferred. When the carboxylic acid component contains an aliphatic dicarboxylic acid, the amount of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 1 mol % or more, more preferably 3 mol % or more, even more preferably 5 mol % or more, and preferably 40 mol % or less, more preferably 30 mol % or less, even more preferably 20 mol % or less.
[0084] An example of the alicyclic dicarboxylic acid is cyclohexanedicarboxylic acid.
[0085] The trivalent or higher polyvalent carboxylic acid is preferably a trivalent carboxylic acid, such as trimellitic acid. The carboxylic acid component may be used alone or in combination of two or more.
[0086] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0087] The amorphous polyester resin B can be produced, for example, by the same method as that for producing the amorphous polyester resin A described above.
[0088] (Physical properties of amorphous polyester resin B) The softening point of the amorphous polyester resin B is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher, and from the viewpoint of low-temperature fixing ability of the toner, is preferably 150°C or lower, more preferably 140°C or lower, and even more preferably 125°C or lower.
[0089] The glass transition temperature of the amorphous polyester resin B is preferably 30° C. or higher, more preferably 40° C. or higher, and even more preferably 50° C. or higher, and from the viewpoint of low-temperature fixing ability of the toner, is preferably 85° C. or lower, more preferably 80° C. or lower, and even more preferably 75° C. or lower.
[0090] The acid value of the amorphous polyester resin B is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, even more preferably 15 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 35 mgKOH / g or less, even more preferably 30 mgKOH / g or less.
[0091] Solubility parameter (SP) of amorphous polyester resin B B (cal / cm 3 ) 1 / 2 From the viewpoint of the chargeability of the toner and reduction of fog in the obtained image, the toner charge is preferably 11.4 (cal / cm 3 ) 1 / 2 More preferably, 11.6 (cal / cm 3 ) 1 / 2 More preferably, 11.8 (cal / cm 3 ) 1 / 2 and preferably 12.4 (cal / cm 3 ) 1 / 2 Less than or equal to 12.2 (cal / cm 3 ) 1 / 2 More preferably, 12.0 (cal / cm 3 ) 1 / 2 The following is the result. The solubility parameter of the amorphous polyester resin B is a solubility parameter according to the Fedors method.
[0092] From the viewpoint of the chargeability of the toner and the reduction of fog in the obtained image, the solubility parameter SP of the amorphous polyester resin B is B and the solubility parameter SP of amorphous polyester resin A A Difference with ΔSP B-A (=SP B -SP A ) is 0.4(cal / cm 3 ) 1 / 2 More preferably, it is 0.5 (cal / cm 3 ) 1 / 2 and 1.5(cal / cm 3 ) 1 / 2 It is preferably 1.2 (cal / cm 3 )1 / 2 Less than or equal to 1.0 (cal / cm 3 ) 1 / 2 Less than 0.8 (cal / cm 3 ) 1 / 2 The following is the result. B-A When there are multiple values for resin A and / or resin B, the smallest ΔSP B-A is preferably within the above range, and any ΔSP B-A is also preferably within the above range.
[0093] The softening point, glass transition temperature, acid value, and solubility parameter of the amorphous polyester resin B can be appropriately adjusted by the type and amount of the raw material monomer used, as well as production conditions such as the reaction temperature, reaction time, and cooling rate. The softening point, glass transition temperature, and acid value of the amorphous polyester resin B can be determined by the method described in the examples. When two or more kinds of amorphous polyester resins B are used in combination, the softening point, glass transition temperature, and acid value of the mixture are preferably within the above-mentioned ranges. As for the solubility parameter, it is sufficient that any one of the resins B is within the above-mentioned range, and it is preferable that all the resins B are within the above-mentioned range.
[0094] The content of the amorphous polyester resin B in the resin particles Y is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, and is 100% by mass or less, preferably 100% by mass.
[0095] [Method for producing resin particle dispersion Y] The resin particles Y are preferably produced by dispersing a resin component containing the amorphous polyester resin B and, if necessary, an optional component such as a surfactant in an aqueous medium to obtain a resin particle dispersion Y. Examples of the method for obtaining the resin particle dispersion Y include the same methods as those for the resin particle dispersion X.
[0096] Before adding the resin particle dispersion Y to the dispersion of aggregated particles 1, an aqueous medium may be added to dilute the dispersion of aggregated particles 1. When the resin particle dispersion Y is added to the dispersion of aggregated particles 1, the aggregating agent may be used in this step to efficiently attach the resin particles Y to the aggregated particles 1. The temperature when resin particle dispersion Y is added is preferably 30° C. or higher, more preferably 35° C. or higher, even more preferably 40° C. or higher, and is preferably 80° C. or lower, more preferably 70° C. or lower, even more preferably 60° C. or lower.
[0097] The resin particle dispersion Y may be added continuously over a certain period of time, may be added all at once, or may be added in several divided portions, but it is preferable to add the resin particle Y continuously over a certain period of time or in several divided portions. By adding the resin particle Y in the manner described above, the resin particle Y is easily selectively attached to the aggregated particles 1. In particular, from the viewpoint of promoting selective attachment and improving the productivity of the toner, it is preferable to add the resin particle Y continuously over a certain period of time. When the resin particle dispersion Y is added continuously, from the viewpoint of obtaining uniform aggregated particles 2 and improving the productivity of the toner, the time is preferably 0.5 hours or more, more preferably 1 hour or more, and preferably 10 hours or less, more preferably 7 hours or less, and even more preferably 3 hours or less.
[0098] From the viewpoints of the chargeability of the toner and reducing fog in the resulting image, the amount of resin particles Y added is an amount such that the mass ratio of resin particles Y to resin particles X (resin particles Y / resin particles X) is preferably 0.01 or more, more preferably 0.04 or more, even more preferably 0.08 or more, and is preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.2 or less.
[0099] From the viewpoints of the electrostatic chargeability of the toner and reducing fog in the obtained images, the content of the amorphous polyester resin B in the toner particles is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and is preferably 25% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less.
[0100] The volume median particle size (D 50 From the viewpoints of the chargeability of the toner and reducing fog in the resulting image, the particle size is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6.5 μm or less.
[0101] Methods for terminating the aggregation include cooling the dispersion, adding an aggregation terminator, diluting the dispersion, and the like.
[0102] [Aggregation Stopper] The aggregation terminator is preferably a surfactant, more preferably an anionic surfactant. Examples of the anionic surfactant include alkylbenzenesulfonate, alkyl sulfate, alkyl ether sulfate, polyoxyalkylene alkyl ether sulfate, arylsulfonate, and arylsulfonic acid formalin condensate. These may be used alone or in combination. The aggregation terminator may be added in the form of an aqueous solution. In the method of adding an aggregation terminator, the amount of the aggregation terminator added is preferably 1 part by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the resin in the aggregated particles 2, from the viewpoint of reliably preventing unnecessary aggregation, and is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, from the viewpoint of reducing residue in the toner.
[0103] <Process 3> In step 3, the aggregated particles 2 obtained in step 2 are fused in an aqueous medium to obtain fused particles. Step 3 is a step in which an amphiphilic molecule having a naphthalene ring is added to the aggregated particles 2 obtained in step 2, and then the temperature is raised to fuse the particles, thereby obtaining fused particles. The amphiphilic molecule having a naphthalene ring is added for the purpose of improving the dispersion stability of the aggregated particles 2 during fusion. The amphiphilic molecule having a naphthalene ring may be present at the time of aggregation in step 1, but it is preferable to add it fresh in step 3 before fusion.
[0104] [Amphiphilic molecules containing a naphthalene ring] The amphiphilic molecule having a naphthalene ring is an amphiphilic molecule having a surface active effect, and is preferably an anionic surfactant. Examples of amphiphilic molecules having a naphthalene ring include naphthalenesulfonates and naphthalenesulfonic acid-formaldehyde condensates. The naphthalenesulfonate is preferably an alkali metal salt of naphthalenesulfonic acid, more preferably sodium naphthalenesulfonate. The naphthalenesulfonic acid-formalin condensate is preferably a compound represented by the following formula (3).
[0105] [ka]
[0106] In formula (3), t represents an integer of preferably 2 or more and 200 or less, more preferably 6 or more and 100 or less, and further preferably 10 or more and 50 or less. M each independently represents a cation, and is a cation of an element selected from the group 1 elements and group 2 elements of the periodic table of elements; quaternary ammonium; and ammonium (NH + Among these, cations of elements in Group 1 of the periodic table of elements are preferred; cations of elements selected from lithium, sodium, and potassium are more preferred, and sodium cations are even more preferred. In addition, it is preferred that multiple M are the same cation. R represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a hydroxyl group, and is preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. In addition, other structural units may be included in the composition as long as the effect as a dispersion stabilizer is not impaired. Examples of other structural units include structural units formed from copolymerizable monomers such as alkyl naphthalene sulfonic acid and alkyl alcohol naphthalene sulfonic acid. The content of these structural units is preferably 30% by mass or less. The naphthalenesulfonic acid-formalin condensate is preferably a sodium salt of a naphthalenesulfonic acid-formalin condensate.
[0107] The weight average molecular weight of the naphthalenesulfonic acid-formalin condensate is preferably 500 or more, more preferably 1,500 or more, even more preferably 2,500 or more, and is preferably 40,000 or less, more preferably 20,000 or less, even more preferably 10,000 or less. The weight average molecular weight of the naphthalenesulfonic acid-formaldehyde condensate is measured by GPC.
[0108] The naphthalenesulfonic acid-formalin condensate can be produced by a known method, for example, by polycondensation using β-naphthalenesulfonic acid (salt) and an equivalent amount of formalin, and other components as necessary, such as sulfonic acids (salts) of β-methylnaphthalene, α-methylnaphthalene, acenaphthene, dibenzofuran, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, and the like. As the naphthalenesulfonic acid-formalin condensate, commercially available products may be used, and examples thereof include DEMOL N, DEMOL NL, DEMOL RN, DEMOL RN-L, DEMOL T, DEMOL T-45, DEMOL MS, DEMOL SN-B, DEMOL SS-L, and DEMOL SC-30 manufactured by Kao Corporation; Labelin AN-40, Labelin F-45, Labelin FC-45, Labelin FC-P, Labelin FD-40, Labelin FP, Labelin FN-P, and Labelin MN-P manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.; and IONET D-2 manufactured by Sanyo Chemical Industries, Ltd.
[0109] The amount of the amphiphilic molecule having a naphthalene ring added in step 3 is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, relative to 100 parts by mass of the aggregated particles 2, and is preferably 35 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less.
[0110] In step 3, from the viewpoint of improving the fusibility of aggregated particles 2, aggregated particles 2 are maintained at a temperature equal to or higher than the glass transition temperature of the resin having the highest glass transition temperature in aggregated particles 2. The holding temperature when fusing the aggregated particles 2 is, from the viewpoint of improving the fusing property of the aggregated particles 2 and improving the productivity of the toner, preferably at least 1° C. higher than the glass transition temperature of the resin having the highest glass transition temperature in the aggregated particles 2, more preferably at least 2° C. higher than the glass transition temperature, and is preferably not higher than 25° C. higher than the glass transition temperature, more preferably not higher than 20° C. higher than the glass transition temperature, and even more preferably not higher than 15° C. higher than the glass transition temperature of the resin having the highest glass transition temperature in the aggregated particles 2. In this case, the time for which the temperature is maintained at or above the glass transition temperature of the resin having the highest glass transition temperature in the aggregated particles 2 is preferably 1 minute or more, more preferably 10 minutes or more, even more preferably 30 minutes or more, and is preferably 240 minutes or less, more preferably 180 minutes or less, even more preferably 120 minutes or less, even more preferably 90 minutes or less. It is preferable to maintain the temperature at the above temperature until the desired circularity is achieved.
[0111] The volume median particle size D of the fused particles obtained by fusion 50 is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6.5 μm or less. The volume median particle size D of the fused particles obtained in step 2 50 is the volume median particle diameter D of aggregate 2 50 It is preferable that the above condition is satisfied. That is, in step 2, it is preferable that aggregation and fusion of aggregated particles 2 do not occur.
[0112] The circularity of the fused particles obtained by fusion is preferably 0.955 or more, more preferably 0.960 or more, even more preferably 0.965 or more, and is preferably 0.990 or less, more preferably 0.985 or less, even more preferably 0.980 or less. The fusion is preferably terminated after the above-mentioned preferred circularity is reached. The circularity is measured by the method described in the Examples.
[0113] <Post-processing process> A post-treatment process may be performed after the fusion process, and the fused particles are isolated to obtain toner particles. Since the fused particles obtained in the fusion process are present in an aqueous medium, it is preferable to first perform solid-liquid separation. For solid-liquid separation, a suction filtration method or the like is preferably used. It is preferable to carry out washing after solid-liquid separation. At this time, it is preferable to remove surfactants other than the block copolymer, so washing with an aqueous medium at a temperature below the cloud point of the surfactant is preferable. It is preferable to carry out washing multiple times. Next, drying is preferably performed. Examples of the drying method include vacuum low-temperature drying, vibration-type fluidized bed drying, spray drying, freeze drying, and flash jet drying.
[0114] [Toner Particles] Volume median particle size of toner particles D 50 From the viewpoint of further improving the cleaning properties of the toner, the particle size is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6.5 μm or less.
[0115] The circularity of the toner particles is preferably 0.955 or more, more preferably 0.960 or more, even more preferably 0.965 or more, and is preferably 0.990 or less, more preferably 0.985 or less, even more preferably 0.980 or less.
[0116] The CV value of the toner particles is preferably 10% or more, more preferably 15% or more, and even more preferably 18% or more, from the viewpoint of improving the productivity of the toner, and is preferably 35% or less, more preferably 30% or less, and even more preferably 25% or less, from the viewpoint of obtaining high-quality images. Volume median particle size of toner particles D 50 The CV value can be measured by the method described in the Examples.
[0117] [Toner for developing electrostatic images] The toner for developing electrostatic images of the present invention has a core-shell structure consisting of a core portion containing an amorphous polyester resin A and a shell portion containing an amorphous polyester resin B, and the amorphous polyester resins A and B are polycondensates of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, and the solubility parameter SP B and the solubility parameter SP of amorphous polyester resin A A Difference with ΔSP B-A is 0.4 or more and 1.5 or less, and a block copolymer of polyethylene glycol and polypropylene glycol is interposed between the core portion and the shell portion. The components contained in the toner of the present invention (essential components) and the components which may be contained in the toner of the present invention (optional components), as well as the components of the toner obtained by the production method of the present invention, are the same as those described above, and therefore the description thereof will be omitted.
[0118] The toner for developing electrostatic images of the present invention comprises toner particles. The toner particles can be used as they are, but it is preferable to use the toner after adding a fluidizing agent or the like as an external additive to the surface of the toner particles.
[0119] [External additives] Examples of the external additive include fine particles of inorganic materials such as hydrophobic silica, titanium oxide, alumina, cerium oxide, and carbon black, and fine particles of polymers such as polycarbonate, polymethyl methacrylate, and silicone resin. Among these, hydrophobic silica is preferred. The external additive may be used alone or in combination of two or more kinds. In addition, two or more kinds of hydrophobic silica having different particle sizes may be used. When the toner particles are surface-treated using an external additive, the amount of the external additive added is, relative to 100 parts by mass of the toner particles, preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4.5 parts by mass or less, even more preferably 4 parts by mass or less.
[0120] Toners are used for developing electrostatic images in electrophotographic printing. The toners can be used, for example, as one-component developers or mixed with a carrier to form two-component developers. EXAMPLES
[0121] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Each property value was measured and evaluated by the following methods. In the notation "alkylene oxide (X)" and the like, the number X in parentheses means the average number of moles of alkylene oxide added.
[0122] [Measurement method] [Softening point, crystallinity index, melting point and glass transition temperature of resin] (1) Softening point Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point. (2) Crystallinity index Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample was weighed into an aluminum pan and cooled to 0°C at a rate of 10°C / min. The sample was then left to stand for 1 minute, and then heated to 180°C at a rate of 10°C / min to measure the amount of heat. The temperature of the peak with the largest peak area among the observed endothermic peaks was taken as the endothermic maximum peak temperature (1), and the crystallinity index was calculated by (softening point (°C)) / (endothermic maximum peak temperature (1) (°C)). (3) Melting point and glass transition temperature Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, and the amount of heat was measured. Among the endothermic peaks observed, the temperature of the peak with the largest peak area was taken as the maximum endothermic peak temperature (2). In the case of a crystalline resin, this peak temperature was taken as the melting point. In the case of an amorphous resin, when a peak was observed, the temperature of the peak was taken as the glass transition temperature. When no peak was observed but a step was observed, the temperature at the intersection of the tangent showing the maximum slope of the curve at the step and an extension of the baseline on the low temperature side of the step was taken as the glass transition temperature.
[0123] [Acid value of resin] The acid value of the resin was measured according to the neutralization titration method described in JIS K 0070: 1992. The measurement solvent was a mixed solvent of acetone and toluene (acetone:toluene=1:1 (volume ratio)).
[0124] [Melting point of release agent] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, the amount of heat was measured, and the maximum endothermic peak temperature was taken as the melting point.
[0125] [Volume median particle diameter D of resin particles, colorant particles, and release agent particles 50 and CV value] (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba Ltd.) (2) Measurement conditions: Put the sample dispersion in a measurement cell, add distilled water, and measure the volume median particle size D at a concentration where the absorbance is in the appropriate range. 50 The volume average particle diameter Dv was measured, and the CV value was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size Dv) x 100
[0126] [Solid Content Concentration of Resin Particle Dispersion, Colorant Particle Dispersion, and Release Agent Particle Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), the moisture content (mass%) of 5 g of the measurement sample was measured at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, moisture content fluctuation range 0.05%). The solid content concentration was calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0127] [Volume median particle diameter of agglomerated particles D 50 〕 Volume median particle size of agglomerated particles D 50 was measured as follows: Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured again, and the volume median particle size D is calculated from the particle size distribution. 50 asked for.
[0128] [Circularity of fused particles] The circularity of the fused particles was measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of fused particles was prepared by diluting with deionized water to a solids concentration of 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode
[0129] [Volume median particle size of toner particles D 50 and CV value] Volume median particle size of toner particles D 50 was measured as follows: The measurement device, aperture diameter, analysis software, and electrolyte were determined based on the volume median particle diameter D 50 The same one used in the measurement was used. Dispersion: Polyoxyethylene lauryl ether "EMULGEN (registered trademark) 109P" (manufactured by Kao Corporation, HLB (hydrophile-lipophile balance) = 13.6) was dissolved in the electrolyte to obtain a dispersion with a concentration of 5 mass %. Dispersion conditions: 10 mg of a measurement sample of dried toner particles was added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Thereafter, 25 mL of the electrolyte was added, and the mixture was further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size D is calculated from the particle size distribution. 50 and volume average particle size D V asked for. The CV value (%) was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size D V ) x 100
[0130] [Resin manufacturing] [Production of amorphous polyester resin] Production Example A1 (Production of Resin A-1) The raw material monomers of polyester resin other than isophthalic acid shown in Table 1, and the esterification catalyst were placed in a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98 ° C was passed, a stirrer, and a thermocouple. Under a nitrogen atmosphere, the reaction system was held at 180 ° C for 1 hour, and then heated from 180 ° C to 230 ° C at 10 ° C / h, and then held at 230 ° C for 5 hours to perform polycondensation. After that, it was cooled to 180 ° C, and isophthalic acid was added to the reaction system, heated from 180 ° C to 230 ° C at 10 ° C / h, reacted at 230 ° C for 1 hour, and reacted at 230 ° C to the softening point shown in Table 1 at 230 ° C, 10 kPa, to obtain resin A-1. The physical properties are shown in Table 1.
[0131] Production Examples A2 and A3 (Production of Resins A-2 and A-3) Resins A-2 and A-3 were obtained in the same manner as in Production Example A1, except that the raw material monomers of the polyester resins shown in Table 1 were changed. The physical property values are shown in Table 1.
[0132] Manufacturing Example B1 (Manufacturing of Resin B-1) The raw material monomers of polyester resin other than fumaric acid shown in Table 1, and the esterification catalyst were placed in a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98 ° C was passed, a stirrer, and a thermocouple. Under a nitrogen atmosphere, the reaction system was held at 180 ° C for 1 hour, then heated from 180 ° C to 230 ° C at 10 ° C / h, and then held at 230 ° C for 5 hours to perform polycondensation. After that, after cooling to 180 ° C, 5 g of fumaric acid and a radical polymerization inhibitor (4-tert-butylcatechol) were added to the reaction system, heated from 180 ° C to 210 ° C at 10 ° C / h, and reacted at 210 ° C for 1 hour, and reacted at 210 ° C and 10 kPa until the softening point shown in Table 1 was obtained. The physical properties are shown in Table 1.
[0133] [Table 1]
[0134] [Production of crystalline polyester resin] Manufacturing Example C1 (Manufacturing of Resin C-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple was replaced with nitrogen, and the raw material monomers of the polyester resin shown in Table 2 were added. The reaction system was heated to 135°C while stirring, and then held at 135°C for 3 hours, and then heated from 135°C to 200°C over 10 hours. Then, 10g of tin(II) di(2-ethylhexanoate) was added to the reaction system, and the system was further held at 200°C for 1 hour, after which the pressure in the flask was reduced and the system was held under a reduced pressure of 8kPa for 1 hour to obtain Resin C-1, a crystalline polyester resin. The physical properties are shown in Table 2.
[0135] [Table 2]
[0136] [Production of resin particle dispersion] Production Example X1 (Production of Resin Particle Dispersion X-1) In a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, 500 g of Resin A-1 and 500 g of methyl ethyl ketone were placed and dissolved for 2 hours at 73° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of Resin A-1 was 80 mol %, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 1500 g of deionized water was added over 60 minutes while stirring at 200 r / min to cause phase inversion emulsification. While maintaining the temperature at 73°C, the methyl ethyl ketone was distilled off under reduced pressure to obtain a dispersion. Thereafter, while continuing to stir, the dispersion was cooled to 30°C, and deionized water was added so that the solid concentration became 25 mass%, thereby obtaining a resin particle dispersion X-1. Volume median particle diameter D of the resin particles in the dispersion 50 and CV values are shown in Table 3.
[0137] Production Examples X2 and X3 (Production of Resin Particle Dispersions X-2 and X-3) Resin particle dispersions X-2 and X-3 were obtained in the same manner as in Production Example X1, except that Resin A-1 in Production Example X1 was changed to the resin shown in Table 3. Volume median particle diameter D of resin particles in the dispersion 50 and CV values are shown in Table 3.
[0138] Production Example X4 (Production of Resin Particle Dispersion X-4) 400g of resin A-1, 100g of resin C-1, and 500g of methyl ethyl ketone were placed in a 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, and dissolved at 73°C for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization was 80 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes. Thereafter, the same procedure as in Production Example X1 was carried out to obtain resin particle dispersion X-4. Volume median particle diameter D of resin particles in the dispersion 50 and CV values are shown in Table 3.
[0139] Production Example Y1 (Production of Resin Particle Dispersion Y-1) 500 g of Resin B-1 and 500 g of tetrahydrofuran were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and dissolved at 40° C. for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization was 60 mol% relative to the acid value of Resin B-1, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 40°C, 1500g of deionized water was added over 60 minutes while stirring at 200r / min (circumferential speed 63m / min) to cause phase inversion emulsification. The obtained solution was heated to 65°C, and tetrahydrofuran was distilled off under reduced pressure to obtain a dispersion. Thereafter, while continuing to stir, the dispersion was cooled to 30°C, and deionized water was added so that the solid concentration became 25% by mass, thereby obtaining a resin particle dispersion Y-1. The volume median particle diameter D of the resin particles in the dispersion 50 and CV values are shown in Table 3.
[0140] Production Example V1 (Production of Resin Particle Dispersion V-1) 100g of resin A-1 and 100g of methyl ethyl ketone were placed in a 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer and nitrogen inlet tube, and resin A-1 was dissolved at 80°C for 1 hour. 5% by mass sodium hydroxide aqueous solution was added to the obtained solution so that the degree of neutralization was 75 mol% with respect to the acid value of resin A-1, and stirred for 30 minutes. Next, while maintaining the temperature at 80°C, 350g of deionized water was added over 60 minutes while stirring at 280r / min (circumferential speed 88m / min), and phase inversion emulsification was performed. While continuing to maintain the temperature at 80°C, methyl ethyl ketone was distilled off under reduced pressure to obtain a dispersion. Thereafter, the dispersion was cooled to 30°C while stirring at 280r / min (circumferential speed 88m / min), and deionized water was added so that the solid content concentration was 20% by mass, thereby obtaining a resin particle dispersion V-1. Volume median particle diameter D of resin particles in the dispersion 50 and CV values are shown in Table 3.
[0141] [Table 3]
[0142] [Production of release agent particle dispersion] Production Example W1 (Production of Release Agent Particle Dispersion W-1) Into a 1 L beaker were added 30 g of deionized water, 100 g of resin particle dispersion V-1, and 50 g of paraffin wax "HNP-9" (manufactured by Nippon Seiro Co., Ltd., melting point 75°C), and the mixture was melted by maintaining the temperature at 90 to 95°C and stirred to obtain a molten mixture. The obtained molten mixture was dispersed for 20 minutes using an ultrasonic homogenizer "US-600T" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) while maintaining the temperature at 90 to 95°C, and then cooled to room temperature (20°C). The solid content was adjusted to 40% by mass with deionized water to obtain a release agent particle dispersion W-1. The volume median particle diameter D of the release agent particles in the dispersion was 50 The diameter was 0.29 μm and the CV value was 37%.
[0143] Production Example W2 (Production of Release Agent Particle Dispersion W-2) A release agent particle dispersion W-2 was obtained in the same manner as in Production Example W1, except that the type of release agent used was changed to Fischer-Tropsch wax "FNP-0090" (manufactured by Nippon Seiro Co., Ltd., melting point 90°C). 50 The diameter was 0.26 μm and the CV value was 39%.
[0144] [Production of colorant particle dispersion] Production Example Z1 (Production of Colorant Particle Dispersion Z-1) In a 1 L beaker, 100 g of copper phthalocyanine pigment "ECB-301" (manufactured by Dainichiseika Chemicals Co., Ltd.), 35 g of polyoxyethylene (13) distyrenated phenyl ether "EMULGEN A-60" (manufactured by Kao Corporation, nonionic surfactant), and 300 g of deionized water were mixed and dispersed for 1 hour at room temperature (20°C) with a stirring blade rotation speed of 8000 rpm using a homomixer "TKAGI HOMOMIXER 2M-03" (manufactured by Tokushu Kika Kogyo Co., Ltd.), and then subjected to 15 PASS treatment at a pressure of 150 MPa using a "Microfluidizer M-110EH" (manufactured by Microfluidics Co., Ltd.), and then passed through a 200 mesh filter, and deionized water was added so that the solid concentration was 20 mass%, to obtain colorant particle dispersion Z-1. The volume median particle diameter D of the colorant particles in the dispersion was 50 The thickness was 0.12 μm and the CV value was 21%.
[0145] The block copolymers of polyethylene glycol and polypropylene glycol (triblock copolymers) used in the examples are shown in Table 4 below. [Table 4]
[0146] [Toner manufacturing] Example 1 (Production of Toner 1) Into a 3 L four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, 400 g of resin particle dispersion X-1, 25 g of release agent particle dispersion W-1, 25 g of release agent particle dispersion W-2, 40 g of colorant particle dispersion Z-1, 1 g of triblock copolymer P-1 (ADEKA Pluronic F108, manufactured by ADEKA Corporation), and 100 g of deionized water were added and mixed at a temperature of 25° C. Next, while stirring the resulting mixture, a solution obtained by dissolving 29 g of ammonium sulfate in 780 g of deionized water and adding a 4.8 mass % potassium hydroxide aqueous solution to adjust the pH to 8.2 was added dropwise over 30 minutes at 25° C., and the temperature was then raised to 55° C. over 1 hour, and the volume median particle diameter D of the aggregated particles was measured. 50 The temperature was maintained at 55° C. until the particle size reached 6.0 μm, thereby obtaining a dispersion of aggregated particles 1. The obtained aggregated particle 1 dispersion was cooled to 50°C, and while maintaining the temperature at 50°C, 60 g of resin particle dispersion Y-1 was added over 90 minutes to obtain aggregated particle 2 dispersion in which the resin particles Y-1 adhered to and aggregated with the aggregated particles 1. To the obtained dispersion of aggregated particles 2, 68 g of a 20 mass % aqueous solution of Demol N (sodium salt of β-naphthalenesulfonic acid formalin condensate, manufactured by Kao Corporation), 670 g of deionized water, and 380 g of a 4.8 mass % aqueous solution of potassium hydroxide were added. The temperature was then raised to 70° C. over one hour, and the temperature was maintained at 70° C. until the circularity reached 0.970, thereby obtaining a dispersion of fused particles in which aggregated particles 2 were fused. The obtained fused particle dispersion liquid was cooled to 30° C., and the solid content was separated by suction filtration, washed with deionized water at 25° C., and then suction filtered for 2 hours at 25° C. Thereafter, the solid content was vacuum dried at 33° C. for 24 hours using a vacuum constant temperature dryer "DRV622DA" (manufactured by ADVANTEC Corporation), to obtain toner particles 1. 100 parts by mass of toner particles 1, 2.5 parts by mass of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 0.04 μm), and 1.0 part by mass of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Japan Co., Ltd., number average particle size: 0.012 μm) were placed in a Henschel mixer, stirred, and passed through a 150 mesh sieve to obtain toner 1. The obtained toner 1 was evaluated as follows. The physical property values of toner particles 1 and the evaluation results of toner 1 are shown in Table 5.
[0147] [Toner Evaluation] [Evaluation of electrostatic charge] At a temperature of 25°C and a relative humidity of 50%, 2.1 g of toner 1 and 27.9 g of silicone ferrite carrier (manufactured by Kanto Denka Kogyo Co., Ltd., average particle size: 40 μm) were placed in a 50 mL cylindrical polypropylene bottle (manufactured by Nikko Hansen Co., Ltd.) and mixed at 250 r / min using a ball mill. Immediately after mixing, the charge amount was measured under the following conditions using a "q / m-meter" (manufactured by Epping Corporation). Mesh size: 635 mesh (opening: 24 μm, stainless steel) Soft blow: Blow pressure (1000V) ·Suction time: 90 seconds The charge amount is calculated by the following formula, and a larger absolute value indicates better chargeability. Charge amount (μC / g) = Total charge after 90 seconds (μC) / Amount of toner absorbed (g)
[0148] [Evaluation of Fog] Toner 1 was mounted on a commercially available printer "Microline (registered trademark) 5400" (manufactured by Oki Electric Industry Co., Ltd.), and an image with a print density of 1% was printed on high-quality paper "J paper A4 size" (manufactured by Fuji Xerox Co., Ltd.) in an environment of a temperature of 25°C and a relative humidity of 50%. This was repeated to print a total of 1000 sheets, and then a blank sheet was printed, during which the printer was stopped midway through the blank sheet printing. The developing unit was removed from the printer, and "Scotch (registered trademark) Mending Tape 810" (manufactured by 3M Japan Ltd., width: 18 mm) was attached to the photoconductor, and Toner 1 on the photoconductor was peeled off with the tape. The tape peeled off from the photoreceptor and unused tape were attached to high-quality paper "J paper A4 size" (manufactured by Fuji Xerox Co., Ltd.), and the tape peeled off from the photoreceptor and unused tape were each measured using a colorimeter "SpectroEye" (manufactured by GretagMacbeth, light irradiation conditions: standard light source D50, observation field of view 2°, density standard DINNB, absolute white standard). The color difference (ΔE) between the tape peeled off from the photoreceptor and unused tape was calculated. The smaller the ΔE value of the toner, the more stable the toner is in obtaining good images with less fog.
[0149] Examples 2 to 7 (Preparation of Toners 2 to 7) In Example 1, triblock copolymer P-1 was changed to triblock copolymers P-2 to P-7, and toner particles 2 to 7 and toners 2 to 7 were obtained in the same manner as in Example 1. Toners 2 to 7 were evaluated in the same manner as toner 1. The physical property values of toner particles 2 to 7 and the evaluation results of toners 2 to 7 are shown in Table 5.
[0150] Examples 8 and 9 (Preparation of Toners 8 and 9) In Example 1, the core resin particle dispersion liquid was changed to X-2 or X-4 as shown in Table 5, and toner particles 8 and 9, and toners 8 and 9 were obtained in the same manner as in Example 1. Toners 8 and 9 were evaluated in the same manner as toner 1. The physical property values of toner particles 8 and 9 and the evaluation results of toners 8 and 9 are shown in Table 5.
[0151] Comparative Examples 1 and 2 (Production of Toners 10 and 11) In Example 1, the triblock copolymer P-1 was changed to 1 g of nonionic surfactant D-1 (polyoxyethylene lauryl ether "EMULGEN 105" (manufactured by Kao Corporation)) or 6.7 g of anionic surfactant D-2 (15 mass % sodium dodecylbenzenesulfonate aqueous solution "NEOPELEX G-15" (manufactured by Kao Corporation)), and toner particles 10 and 11, and toners 10 and 11 were obtained in the same manner as in Example 1. Toners 10 and 11 were evaluated in the same manner as toner 1. The physical property values of toner particles 10 and 11 and the evaluation results of toners 10 and 11 are shown in Table 5.
[0152] Comparative Example 3 (Production of Toner 12) In Example 1, the core resin particle dispersion liquid was changed to X-3 as shown in Table 5, and toner particles 12 and toner 12 were obtained in the same manner as in Example 1. Toner 12 was evaluated in the same manner as toner 1. The physical property values of toner particles 12 and the evaluation results of toner 12 are shown in Table 5.
[0153] [Table 5]
[0154] From Table 5, ΔSP B-A It can be seen that the toner obtained through step 1 of obtaining aggregated particles 1 in the presence of a block copolymer of polyethylene glycol and polypropylene glycol using amorphous polyester resin A and amorphous polyester resin B having a refractive index of 0.4 or more and 1.5 or less has excellent charging properties, and images with little fog can be stably obtained using the toner (Examples 1 to 9). In contrast, when aggregated particles 1 were obtained in the presence of polyoxyethylene lauryl ether instead of the block copolymer of polyethylene glycol and polypropylene glycol (Comparative Example 1), and when aggregated particles 1 were obtained in the presence of sodium dodecylbenzenesulfonate (Comparative Example 2), ΔSP B-A It is seen that when is less than 0.4 (Comparative Example 3), the resulting toner has low chargeability and large ΔE, resulting in a large amount of fog in the resulting image.
Claims
1. A method for producing a toner for developing an electrostatic image having a core-shell structure comprising a core portion containing an amorphous polyester resin A and a shell portion containing an amorphous polyester resin B, comprising the steps of: The amorphous polyester resins A and B are polycondensates of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, Solubility parameter SP of amorphous polyester resin B B and the solubility parameter SP of amorphous polyester resin A A Difference ΔSP B-A is 0.4 (cal / cm 3 ) 1/2 More than 1.5 (cal / cm 3 ) 1/2 is as follows: A method for producing a toner for developing an electrostatic image, comprising the following steps 1 to 3 in this order: Step 1: A step of aggregating resin particles X containing an amorphous polyester resin A in an aqueous medium in the presence of a block copolymer of polyethylene glycol and polypropylene glycol to obtain aggregated particles 1. Step 2: A step of adding resin particles Y containing a non-crystalline polyester resin B to the aggregated particles 1 obtained in step 1 to obtain aggregated particles 2. Step 3: A step of fusing the aggregated particles 2 obtained in step 2 to obtain fused particles.
2. Solubility parameter SP of amorphous polyester resin A A is 10.7 (cal / cm 3 ) 1/2 More than 11.6 (cal / cm 3 ) 1/2 The method for producing a toner for developing an electrostatic image according to claim 1, wherein the toner is:
3. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein the amorphous polyester resin A is a polycondensate of an alcohol component containing 60 mol % or more of neopentyl glycol and a carboxylic acid component.
4. 4. The method for producing a toner for developing electrostatic images according to claim 1, wherein the block copolymer of polyethylene glycol and polypropylene glycol is a polyethylene glycol-polypropylene glycol-polyethylene glycol type triblock copolymer.
5. A method for producing a toner for developing an electrostatic image having a core-shell structure, the core portion including an amorphous polyester resin A and a crystalline polyester resin C, and a shell portion including an amorphous polyester resin B, comprising:
5. The method for producing a toner for developing an electrostatic image according to claim 1, wherein step 1 is a step of aggregating resin particles X, the resin particles X including an amorphous polyester resin A and a crystalline polyester resin C in the same or different particles, in an aqueous medium in the presence of a block copolymer of polyethylene glycol and polypropylene glycol to obtain aggregated particles 1.
6. A toner for developing electrostatic images having a core-shell structure comprising a core portion containing an amorphous polyester resin A and a shell portion containing an amorphous polyester resin B, The amorphous polyester resins A and B are polycondensates of an alcohol component containing 80 mol % or more of an aliphatic diol and a carboxylic acid component, Solubility parameter SP of amorphous polyester resin B B and the solubility parameter SP of amorphous polyester resin A A Difference ΔSP B-A is 0.4 (cal / cm 3 ) 1/2 More than 1.5 (cal / cm 3 ) 1/2 is as follows: A toner for developing electrostatic images, comprising a block copolymer of polyethylene glycol and polypropylene glycol interposed between a core portion and a shell portion.
Citation Information
Patent Citations
toner
JP2008089913A
toner
JP2008129282A